1999
DOI: 10.1099/13500872-145-5-1115
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Aspergillus nidulans gene expression induced by bafilomycin, a Streptomyces-produced antibiotic

Abstract: In natural environments bacteria and filamentous fungi often compete for the same resources. Consequently, production of antibiotic secondary metabolites and defence mechanisms against these compounds have evolved in these organisms. An experimental model has been developed to study the response in fungi exposed to one such antibiotic. The filamentous fungus Aspergillus nidulans was treated with bafilomycin B, , a Streptomyces-produced antibiotic which reduces radial growth rate and induces morphological chang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2002
2002
2011
2011

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 20 publications
1
22
0
Order By: Relevance
“…The bafilomycins, and the closely related concanamycins, are inhibitors of vacuolar ATPases, produced by various Streptomyces species (Bowman et al 1988;Dro¨se and Altendorf 1996). Previously, we used the mRNA differential display technique (RNA-DD; Liang and Pardee 1992) to screen for genes in Aspergillus nidulans that exhibited changes in expression upon treatment with bafilomycin B1 (Melin et al 1999). We found that the antibiotic up-regulated the expression of three genes, whereas the expression of two genes was down-regulated.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The bafilomycins, and the closely related concanamycins, are inhibitors of vacuolar ATPases, produced by various Streptomyces species (Bowman et al 1988;Dro¨se and Altendorf 1996). Previously, we used the mRNA differential display technique (RNA-DD; Liang and Pardee 1992) to screen for genes in Aspergillus nidulans that exhibited changes in expression upon treatment with bafilomycin B1 (Melin et al 1999). We found that the antibiotic up-regulated the expression of three genes, whereas the expression of two genes was down-regulated.…”
Section: Introductionmentioning
confidence: 99%
“…The difference in gene expression varied from 10-fold to one extreme case in which expression of the gene in question was only detectable in the bafilomycin-treated fungus. At that time, the biological functions of most of these five genes were unknown (Melin et al 1999). However, one of the down-regulated genes was later found to encode a cell wall-associated zinc-binding protein, Aspnd1 (Segurado et al 1999).…”
Section: Introductionmentioning
confidence: 99%
“…AF104 does not appear to have an ortholog in the pax gene cluster. Although AF106 has a very small open reading frame (encoding 87 amino acids), the predicted polypeptide shares significant similarity with the C terminus of A. nidulans AN6743 and with A. nidulans BinA, with the latter being defined as functional by the isolation of an expressed sequence tag (27 3-kb BamHI fragment of pSZ-21 containing ggsA was subcloned into pBluescript II KS(ϩ) to generate pSZ-22, which was used as a template to extend the sequence data previously derived from the 218-bp insert in pSZ-2. This sequence (ggsA) contained the five conserved domains found in other prenyl diphosphate synthase genes (8) and had significant identity to paxG (E value of 5eϪ40).…”
Section: Vol 70 2004 Indole-diterpene Biosynthetic Genes In a Flavmentioning
confidence: 99%
“…Indeed, various studies have used "omics" techniques to probe the changes that occur during BFIs at the subcellular level (25,94,167,231,235,259,281,352); for example, a recent study of the arbuscular mycorrhizal fungus Gigaspora margarita using combined proteomic and lipid metabolite profiling revealed that the presence of endobacteria had a significant impact on fungal physiology (331). Targeted approaches assessing the proteomic or transcriptomic responses of one BFI partner to molecules produced by the other also allow the testing of specific hypotheses relating to BFIs, such as responses to antibiotics (245,246). However, many mechanistic investigations of BFIs are performed in controlled microcosms with a very limited number of interacting microorganisms, whereas natural interactions often involve a complex community of microorganisms whose combined properties may be unpredictable.…”
Section: Consequences Of Bacterial-fungal Interactions For Participatmentioning
confidence: 99%